Making food safety interventions benefit the most vulnerable urban consumers in Vietnam and Cambodia - Minh Cam Duong; Hung Nguyen-Viet; Tum, S.; Young, M.F. (International Livestock Research Institute, 2023)
This research brief characterizes food access, food safety perception, and food acquisition behaviours among low-income urban households in Vietnam and Cambodia and proposes how to harness the benefits of market-based food safety interventions to improve household access to safe food.